Approximation of the classes C_β^ψ H_ω by generalized de la Valiée-Poussin sums - Novikov, O. A.; Rukasov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
On the classes of periodic functions C_β^ψ H_ω, we study approximating properties of trigonometric polynomials generated by methods for summation of Fourier series.